EVALUATION OF QUALITY OF THE VIRGIN COCONUT OIL EXTRACTED BY TRADITIONAL AND COLD CENTRIFUGATION METHODS - E. M. NIVYA (The Journal of Research ANGRAU, 2023)
The study was conducted in the year 2022 to assess the quality of VCO obtained using various extraction methods. VCO was extracted from fresh and mature kernels of the Kerasree coconut variety using traditional (TVCO) and cold centrifugation (CCVCO) methods. TVCO showed the highest mean score of 8.99 for overall acceptance based on the organoleptic evaluation. Physicochemical properties of VCOs were statistically analysed and compared to the guidelines for edible oils established by the Asian Pacific Coconut Community (APCC). The findings revealed that there was a significant difference (p